A Catalogue of Indian Hydraenidae (Insecta: Coleoptera) - Ghosh, Joyjit; Saini, Jagdish; Gupta, Devanshu; Ghosh, Sujit Kumar; Chandra, Kailash (Zootaxa, 2022)
This catalogue lists 46 valid species included in 7 genera and two subfamilies of the family Hydraenidae (Coleoptera), recorded from India. The subfamily Hydraeninae accommodates 24 species (5 genera), and Ochthebiinae 22 species (2 genera). We include synonyms, type localities, type depositories, and distribution of the species. The Himalayan region supports the maximum diversity (31 species), followed by Deccan Peninsula (5 species), Western-Ghats (5 species), Northeast (4 species), Gangetic Plains (4 species), Semi-Arid (2 species), and Islands (one species).